2015
DOI: 10.1016/j.aap.2015.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Real-time driver drowsiness feedback improves driver alertness and self-reported driving performance

Abstract: Driver drowsiness has been implicated as a major causal factor in road accidents. Tools that allow remote monitoring and management of driver fatigue are used in the mining and road transport industries. Increasing drivers' own awareness of their drowsiness levels using such tools may also reduce risk of accidents. The study examined the effects of real-time blink-velocity-derived drowsiness feedback on driver performance and levels of alertness in a military setting. A sample of 15 Army Reserve personnel (1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…Fatigue is manifested in performance decline, feelings of exhaustion, and body resource depletion. The negative impact of fatigue on decision performance (Aidman, Chadunow, Johnson, & Reece, ; Jackson, Kleitman, & Aidman, ; Johnson et al, ; Pilcher & Huffcutt, ) has been consistently reported as a primary factor underlying the decision errors that can lead to real‐world catastrophes. Decision making is known to be affected by the output of cognitive processing and by metacognitive monitoring and control of decision behaviours (e.g., Ackerman & Wolman, ; Cheng, Tallent, Bender, Tran, & Drake, ; Jackson, Kleitman, Stankov, & Howie, ; Koriat & Goldsmith, ; Stanovich & West, ; Thompson, Turner, & Pennycook, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is manifested in performance decline, feelings of exhaustion, and body resource depletion. The negative impact of fatigue on decision performance (Aidman, Chadunow, Johnson, & Reece, ; Jackson, Kleitman, & Aidman, ; Johnson et al, ; Pilcher & Huffcutt, ) has been consistently reported as a primary factor underlying the decision errors that can lead to real‐world catastrophes. Decision making is known to be affected by the output of cognitive processing and by metacognitive monitoring and control of decision behaviours (e.g., Ackerman & Wolman, ; Cheng, Tallent, Bender, Tran, & Drake, ; Jackson, Kleitman, Stankov, & Howie, ; Koriat & Goldsmith, ; Stanovich & West, ; Thompson, Turner, & Pennycook, ).…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, it may be difficult to keep the driver alert long enough to safely reach a destination, so countermeasures may need to promote the driver to take a break to rest. It is unclear what type of feedback might work best to promote longer-term behavioral change (though see Aidman et al 2015). The next phase of this NHTSA-sponsored research program is currently investigating the effectiveness of drowsiness countermeasures over longer drives.…”
Section: Discussionmentioning
confidence: 99%
“…There is the ongoing research on mobile devices that can be built into cars and analyze some physiological parameters (e.g., percentage of eyelid closure, blink velocitybased score, average pupil diameter, electroencephalogram (EEG) signal, standard deviation of lateral position and steering wheel reversals) to warn a driver in advance [24][25][26].…”
Section: Discussionmentioning
confidence: 99%